CREATIVE DIRECTION OF IKA MAHARDIKA IN THE PREPRODUCTION OF THE UNREMEMBERED DOCUMENTARY FILM - Syam, St. Hadidja; Afrianto, Damar Tri; Wastiwi S, Sri (Capture : Jurnal Seni Media Rekam, 2019)
This study aims to describe Ika Mahardika's creative process in directing the documentary film The Unremembered, especially in the preproduction stage. The research method uses descriptive qualitative. The results showed that director Ika Mahardika's creativity in digging data about Salawati Daud lies in the ability to use ethnographic research methods in a coherent manner starting from literature search, field observations, interviews and documents. In addition, Ika Mahardika's creativity also lies in data processing starting from selecting data with consideration of the capacity of the information provided then how the data is displayed chronologically.